CALCULATION OF COST OF PRODUCTION TYPE 36 HOUSE AT PT. DZAKA ROTSA PROPERTY - Friska Putri Rahayu; Muslimin Abdul Rahim (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
Research at PT. Dzaka Rotsa Properti shows that there is a significant price difference with other housing in the same area, making Akhtara Residence owned by PT. Dzaka Rotsa Properti cannot compete because the selling price offered is more expensive. Research shows that there is no correct classification of costs, the company also has not classified factory overhead costs in detail according to the cost accounting concept, as a result the company has not been in accordance with the calculation of the cost of production which can affect the selling price and the profit achieved. The production process which is carried out on an order basis and still uses manual labor for earthworks makes the required cost even greater. From these problems, it is necessary to have an alternative to accelerate development to shorten the time and reduce the budget for development costs as well as to plan and calculate the cost of production according to the cost accounting concept using the full-costing order cost method. According to the company's production costs in producing one type 36 housing unit, the total RAB is Rp. 150,600,000. Meanwhile, according to research results based on calculations after accelerating development in accordance with the cost accounting concept, the raw material costs are Rp. 144,545,348, direct labor costs are Rp. 16,063. 333, and factory overhead costs of Rp. 21,685,500 plus the difference in factory overhead costs of Rp. 6,582. The profit calculated by the company is Rp. 38,400,000, while according to research it is Rp. 86,458,234. So there is a difference in calculations between the company and researchers of Rp. 48,058,834.